The Effect of Mixed Method Training according to some muscle work indicators to Develop Achievement in power lifting Lifters - Qusay, Mohammed (Journal of Physical Education, 2010)
The Importance of This research that comes out of the usage of mixing way to upgrade the level of the a achievement of the power lifting so the researcher can observe through his experience and the interview that he made it with many coaches of the physical strength that there is some lacking of using this important way that focus on muscle strength way and that identify mixing way that the most coaches use it for the movable way and fixed way with individually and isolation from others so the researcher will apply prepare training method that the way will put two methods that will make the positives of two ways and avoid some negatives , including providing for coaches not fine any boring to them . The sample of research are kadumia and Saidia club which category of youth within legal weights for sport of power lift of Baghdad champions that kadumia club represents the Control group and saidia club represents experimental group .After identify the special test for research and apply for training method to experimental group that lead a researcher for several results as following: The experimental method in positive way on the independence group that the result was good between before and after but the result was to result before and rate of development was to experimental group for sport of physical strength that it depends simple change to break the record especially the sample was for weight lifter champions that is too hard to effect on them and one of them got the Arabic record and that indicate for importance of result that researcher could reach of his research and the result was randomly between the two group and the researcher could notice the most people and champions can be from Iraq and Baghdad that means is deference between two group two groups as the method result